2014
DOI: 10.1007/s00259-014-2782-y
|View full text |Cite
|
Sign up to set email alerts
|

11C-ORM-13070, a novel PET ligand for brain α2C-adrenoceptors: radiometabolism, plasma pharmacokinetics, whole-body distribution and radiation dosimetry in healthy men

Abstract: (11)C-ORM-13070 was rapidly metabolized in human subjects after intravenous injection. The effective radiation dose of (11)C-ORM-13070 was in the same range as that of other (11)C-labelled brain receptor tracers. An injection of 500 MBq of (11)C-ORM-13070 would expose a subject to 2.0 mSv of radiation. This supports the use of (11)C-ORM-13070 in repeated PET scans, for example, in receptor occupancy trials with novel drug candidates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…A PET tracer for a 2C adrenoceptors is expected to be useful for preclinical and clinical drug development (20). The tracer has been introduced to human use (21,22), as evidenced by 4 already completed clinical PET trials with 11 C-ORM-13070 (ClinicalTrials. gov identifiers NCT00735774, NCT00829907, NCT01435213, and NCT01794975).…”
Section: Discussionmentioning
confidence: 99%
“…A PET tracer for a 2C adrenoceptors is expected to be useful for preclinical and clinical drug development (20). The tracer has been introduced to human use (21,22), as evidenced by 4 already completed clinical PET trials with 11 C-ORM-13070 (ClinicalTrials. gov identifiers NCT00735774, NCT00829907, NCT01435213, and NCT01794975).…”
Section: Discussionmentioning
confidence: 99%
“…This compound has a binding affinity selectivity of over 200-fold vs. the α 2A -AR, with weak or no activity at more than 100 other potential target sites and receptors, and will be highly valuable for facilitating forward and reverse translation between animal and human studies. An obvious application is determination of target engagement, through conducting receptor occupancy studies for novel drug candidate molecules for preclinical and clinical studies ( 62 , 245 , 246 ). However, it could also be used to gain more precise insight on the relative α2C -AR occupancy for antipsychotic (e.g., clozapine) and antidepressant (e.g., mirtazapine) agents at clinical doses thus enabling a better understanding on the mode of action of these drugs.…”
Section: Future Perspective: What Do We Have and What Do We Need?mentioning
confidence: 99%
“…These studies revealed that [ 11 C]ORM‐13070 penetrated rapidly into the brain with the most prominent accumulation of radioactivity occurring in the caudate nucleus and putamen. The test–retest reliability of the uptake was good, with absolute variability of 4.3% in the putamen and 6.5% in the caudate nucleus (Lehto et al, ; Luoto et al, ).…”
Section: Introductionmentioning
confidence: 99%